6x+13=69-3x

Simple and best practice solution for 6x+13=69-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+13=69-3x equation:


Simplifying
6x + 13 = 69 + -3x

Reorder the terms:
13 + 6x = 69 + -3x

Solving
13 + 6x = 69 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
13 + 6x + 3x = 69 + -3x + 3x

Combine like terms: 6x + 3x = 9x
13 + 9x = 69 + -3x + 3x

Combine like terms: -3x + 3x = 0
13 + 9x = 69 + 0
13 + 9x = 69

Add '-13' to each side of the equation.
13 + -13 + 9x = 69 + -13

Combine like terms: 13 + -13 = 0
0 + 9x = 69 + -13
9x = 69 + -13

Combine like terms: 69 + -13 = 56
9x = 56

Divide each side by '9'.
x = 6.222222222

Simplifying
x = 6.222222222

See similar equations:

| 1/3(5-3x)=5/6(x-2) | | x-39=79 | | 6(3x-12)=54x | | 13x+12=5x+10 | | 5m+20=6m+12 | | -3(x-2.7)=1.8 | | 5y^2-17y+14= | | -5x^2-5x+10=-2x^2-4x+7 | | 7(x-3)=-4x+89 | | 8.4=-6(a+2.4) | | -3x^2-11x+5=-4x+6 | | 236-6x=39x+16 | | 5m=-2+3m | | m/6-1.5=-7 | | 6x+20=38 | | 4t-5tu= | | 4x-6=-16-7 | | 4-3x=-1x+4-2x | | r-1.3=1.1 | | 7x+3(x+4)=-18 | | 5x-4=-2+3x | | 158-2x=34x+22 | | x^2-14x+29=-3x+5 | | 8m^2-16m+8=0 | | 12-7x=177-42x | | x^2-18x+40=-5x | | 3x+36=5x*12 | | 7a+3=2a+8 | | 7x-6=70 | | x-x/10=189 | | 3y^3+2y^2-9y-6= | | k-3.5=21 |

Equations solver categories